ANALISIS EFISIENSI TEKNIS PENGGUNAAN INPUT PRODUKSI PADA USAHATANI PADI LADANG DI DESA KALAMBA KECAMATAN HAHARU KABUPATEN SUMBA TIMUR - Panu, Stepanus Reku; Wadu, Junaedin (Agros Journal of Agriculture Science, 2024)
This study aims to analyze the technical efficiency of upland rice farming in the village of Kalamba. This research was conducted in Kalamba Village, Haharu District, East Sumba Regency. The number of samples used in this study were 50 farmers who were field rice farmers in the village of Kalamba. This study uses multiple linear regression with the production function of the Cobb-Douglas model to analyze the factors that influence upland rice production. To determine the level of technical efficiency in the use of production inputs in farming, an analysis is carried out using the technical efficiency equation with the Cobb-Douglas model function. The results of the analysis explained that the variables of land area and seeds had a significant effect on the amount of field rice production. Meanwhile, urea fertilizer and labor did not have a significant effect on the total production of lowland rice farming in Kalamba Village, Haharu District, East Sumba Regency. The average value of technical efficiency of upland rice farming in Kalamba Village is 0.71. The average efficiency value is still below 1, meaning that technically upland rice farming is not efficient. Keywords: Field rice, Production, Efficiency, Production inputs. INTISARIPenelitian ini bertujuan untuk menganalisis efisiensi teknis usahatani padi gogo di Desa Kalamba. Penelitian ini dilakukan di Desa Kalamba, Kecamatan Haharu, Kabupaten Sumba Timur. Jumlah sampel yang digunakan dalam penelitian ini adalah 50 orang petani yang merupakan petani padi sawah di Desa Kalamba. Penelitian ini menggunakan regresi linier berganda dengan fungsi produksi model Cobb-Douglas untuk menganalisis faktor-faktor yang mempengaruhi produksi padi gogo. Untuk mengetahui tingkat efisiensi teknis penggunaan input produksi pada usahatani, dilakukan analisis menggunakan persamaan efisiensi teknis dengan fungsi model Cobb-Douglas. Hasil analisis menjelaskan bahwa variabel luas lahan dan bibit berpengaruh nyata terhadap jumlah produksi padi sawah. Sedangkan pupuk urea dan tenaga kerja tidak memberikan pengaruh yang nyata terhadap total produksi usahatani padi sawah di Desa Kalamba Kecamatan Haharu Kabupaten Sumba Timur. Nilai rata-rata efisiensi teknis usahatani padi gogo di Desa Kalamba sebesar 0,71. Nilai efisiensi rata-rata masih dibawah 1, artinya secara teknis usahatani padi gogo belum efisien. Kata Kunci : Padi Sawah, Produksi, Efisiensi, Input Produksi.